A case study: The energy performance gap of the Center for Interactive Research on Sustainability at the University of British Columbia. (December 2015) - Salehi, M. Mahdi; Terim Cavka, Belgin; Frisque, Andrea; Whitehead, Derek; Bushe, W. Kendal
Abstract: This work is a case study of the energy performance gap in a LEED Platinum-certified university building. Comparing the whole-building energy modeling results with the overall measured energy consumption, the building shows approximately 60% higher energy consumption during its first year of operation than the initial model prediction. The building is heavily instrumented and a large amount of detailed data is logged, providing a unique opportunity to compare energy model prediction to actual building performance and operations. Energy performance gaps of this magnitude are commonly found and the reasons are not yet well understood. There are many potential sources for discrepancies: different usage of the building in model and reality, design, construction and commissioning deficiencies, software limitation and modeling errors and different weather in reality than in the model are the factors typically considered. To better understand the nature of the performance gap, potential sources of discrepancy between model and measurement have been eliminated in a series of steps, to evaluate their significance in the case of this particular building, starting with eliminating the most intrinsic prediction challenge to any energy model – the weather – and continuing toward increased controllability and interdependence: occupancy, lighting and equipment loads, envelope performance, mechanical systems and ventilation. The present paper shows that in the case of the CIRS building the major sources of the performance gap are that the building has been built and is operated differently from what was expected. A major component of the CIRS energy concept is heat exchange with a neighboring building; however, because of design and commissioning deficits, the heat exchange falls short of the design intent. Furthermore, a waste water treatment plant located in the building is on the building's meters and included in the measured data, but not in the energy model. The transformers' electricity consumption was not in the energy model either and they were significantly inefficient. Part of the building's unanticipated usage is large lighting and plug loads. Abstract : Highlights: CIRS is a LEED Platinum-certified building with significant energy performance gap. The building is heavily instrumented providing a unique opportunity to study the gap. Results show that waste water treatment plant was not in the LEED energy model. Part of the building's unexpected usage is lighting, plug load and transformers. Heat exchange with neighboring building was not designed and commissioned properly.